Automobile seat breathable sweat-absorbing sound-proof foam and preparation method thereof
Patent Information
- Application Number
- CN202411979451.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]针对现有技术的不足,本发明提供了一种汽车座椅透气吸汗防音泡棉及其制备方法,解决了汽车座椅泡棉材料中孔隙结构不均匀、多功能性能协同性不足及制备工艺精确性不高的问题
1、本发明通过动态交联调控剂与铂金催化剂的协同作用,在低黏度与高黏度乙烯基硅油的交联反应中逐步构建稳定的动态网络结构,达到了同时兼顾泡棉加工流动性与孔隙结构稳定性的技术效果。相较于现有技术中单一交联方式导致交联不均匀或反应速率失控的问题,本发明解决了交联速率难以控制以及泡棉孔隙不均匀的不足,显著提高了泡棉的力学性能与使用可靠性。
Smart Images

Figure CN122917541A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-performance foam materials technology, specifically to a breathable, sweat-absorbing, and sound-absorbing foam for automotive seats and its preparation method. Background Technology
[0002] With the continuous development of the automotive industry, consumers are increasingly demanding higher standards for the comfort, functionality, and environmental performance of the in-car environment. This is especially true during long drives or in extreme weather conditions, where the breathability, sweat absorption, sound insulation, and flame retardancy of seat materials become paramount. Existing automotive seat foam materials typically use silicone oil as the main material and employ foaming processes to create a porous structure, enhancing the material's softness and functionality. These materials can, to a certain extent, meet basic requirements such as breathability and flexibility, while adding fillers such as silica and flame-retardant powder improves mechanical and flame-retardant properties. Current technologies also utilize various foaming processes (such as physical and chemical foaming) to achieve material lightweighting and attempt to optimize pore structure distribution through gas concentration control. However, due to limitations in process and formulation design, existing foam materials still have room for improvement in terms of functional optimization and performance synergy.
[0003] Despite some progress in the research and application of automotive seat foam materials, existing technologies still face several insurmountable shortcomings in practical applications. For example, the pore structure of existing foam materials is often not uniform, with some areas having pores that are too large or too small, leading to inconsistent performance in breathability, sweat absorption, and sound insulation. Furthermore, the foaming process suffers from relatively crude control over gas concentration and expansion rate, resulting in a mismatch between bubble formation rate and cross-linking reaction rate, affecting the stability of the pore network. Simultaneously, the selection and use of fillers and flame-retardant powders are largely limited by traditional designs, resulting in poor dispersibility and compatibility, making it difficult to achieve a balance of multiple functional properties. A more prominent issue is that existing foams are mostly designed with uniform thickness, lacking gradient optimization for different functional requirements, leading to insufficient multi-functional properties and making it difficult to fully meet the high demands of automotive seats for breathability, sweat absorption, sound insulation, and flame retardancy. In addition, the current manufacturing processes lack precision in controlling key parameters, resulting in poor consistency in material performance. These shortcomings limit the further promotion and application of existing automotive seat foam materials in the high-end market. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a breathable, sweat-absorbing, and sound-absorbing foam for automotive seats and its preparation method, solving the problems of uneven pore structure, insufficient synergy of multifunctional properties, and low precision in the preparation process of automotive seat foam materials.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a breathable, sweat-absorbing, and sound-absorbing foam for car seats, comprising...
[0006] Preferably, the following components are used: 50-70 parts of low-viscosity vinyl silicone oil; 30 to 50 parts of high-viscosity vinyl silicone oil; 90 to 130 parts of silica; 140-160 parts of aluminum-based flame retardant powder; 1 to 3 parts of dynamic crosslinking regulator; Catalyst: 0.3 to 0.5 parts; Pore orienting agent: 1.5 to 3 parts; 10 to 30 parts filler; 5 to 15 parts of gas inducer; Low-viscosity vinyl silicone oil is a highly fluid silicone oil base material with good reactivity. It can react rapidly with dynamic crosslinking regulators to form a preliminary crosslinking network. 50 to 70 parts of low-viscosity vinyl silicone oil can provide basic flowability and processability for foam. Below 50 parts, the overall viscosity of the system is too high, making it difficult to mix thoroughly; above 70 parts, the crosslinking network density is insufficient, leading to a decrease in the mechanical strength and porosity control of the foam. High-viscosity vinyl silicone oil is used to enhance the structural support of the system and provide the necessary strength and elasticity to the pore walls of the foam. A range of 30 to 50 parts ensures that the proportion of high-viscosity vinyl silicone oil in the foam is moderate, thus forming a gradient structure when combined with low-viscosity silicone oil without making the overall viscosity of the system too high, affecting processability. Below 30 parts, the structural support of the foam is insufficient; above 50 parts, the mixing uniformity is affected.
[0007] Silica is an ultrafine silica powder used to regulate the pore size and distribution of a system, while increasing the mechanical strength and surface hardness of foam. A range of 90 to 130 parts per part provides good support during the bubble nucleation stage, preventing bubble collapse. Below 90 parts per part, the foam's pore control is insufficient, leading to uneven pore distribution; above 130 parts per part, the system viscosity may become too high, affecting the foaming effect and the material's flexibility.
[0008] Aluminum-based flame retardant powder absorbs heat and releases moisture, providing excellent flame retardant performance at high temperatures. It also fills and reinforces the foam structure. 140-160 parts of aluminum-based flame retardant powder ensures flame retardant performance while minimizing impact on foam flexibility. Below 140 parts, the flame retardant performance is difficult to achieve; above 160 parts, the material's toughness and foaming properties significantly decrease.
[0009] Dynamic crosslinking regulators (such as thiol compounds) are reaction control agents that can regulate the crosslinking rate of vinyl silicone oil, thereby forming a stable dynamic crosslinking network. A range of 1 to 3 parts can achieve a balance between the crosslinking rate and reaction stability. When the amount is less than 1 part, the crosslinking reaction is insufficient, leading to a decrease in the mechanical properties of the foam; when the amount is more than 3 parts, the crosslinking rate is too fast, making it difficult to control the uniformity of the pore structure.
[0010] The catalyst (platinum catalyst) is used to accelerate the crosslinking reaction of vinyl silicone oil and improve the reaction efficiency of the system. 0.3 to 0.5 parts (equivalent to 3000 ppm to 5000 ppm) of platinum catalyst can efficiently promote the crosslinking reaction while controlling the reaction rate. Below 0.3 parts, the crosslinking efficiency is insufficient; above 0.5 parts, the catalyst dosage is too high, which increases costs and is prone to premature reaction.
[0011] Pore-orienting agents (such as fluorinated block copolymers) reduce interfacial tension, regulate the nucleation sites and uniform distribution of bubbles, and 1.5 to 3 parts of pore-orienting agent can effectively form a uniform pore structure. When the amount is less than 1.5 parts, bubbles are prone to coalescence or collapse; when the amount is more than 3 parts, the bubbles may become too small and difficult to connect, affecting air permeability.
[0012] Fillers (such as porous carbon-based materials) are used to enhance the adsorption and sound insulation properties of foam, while also improving the mechanical properties of the material. A range of 10 to 30 parts can ensure a balance between the sound insulation and sweat absorption properties of the foam. Below 10 parts, the adsorption performance is insufficient; above 30 parts, the viscosity of the system is too high, and the foaming performance is affected.
[0013] Preferably, the gas conditioning system used for the component materials includes: The primary foaming gas is CO2, with a concentration of 1% to 3%. The foaming gas NH3 has a concentration of 0.5% to 1.5%. The gas inducer is expandable polystyrene microspheres with a particle size range of 5 μm to 10 μm; The catalyst used is a platinum catalyst; The primary foaming gas CO2 provides the initial conditions for bubble formation, while the expanding foaming gas NH3 further expands the pore structure and enhances pore connectivity. The gas inducer (expandable polystyrene microspheres) expands during heating, significantly improving the uniformity and controllability of pore formation. The platinum catalyst ensures the efficient execution of the crosslinking reaction, supporting the stability of the pore structure. This claim refines the key steps of the foaming process and improves the precision of pore structure control.
[0014] Preferably, the viscosity of the low-viscosity vinyl silicone oil is 500 mPa·s-800 mPa·s, the viscosity of the high-viscosity vinyl silicone oil is 1000 mPa·s-3000 mPa·s, the pore orientation agent is a fluorinated block copolymer, and the dynamic crosslinking regulator is a mercapto compound. By defining the viscosity ranges of low-viscosity and high-viscosity vinyl silicone oils, a balance between material flowability and crosslinking network construction was ensured. At the same time, the selection of pore orienting agents and dynamic crosslinking regulators was further clarified, optimizing the distribution of pore structure and crosslinking reaction rate.
[0015] Preferably, the silica is fumed silica with a particle size range of 5 nm to 15 nm, and the filler is a porous carbon-based material with a specific surface area of 500 m². 2 / g~1500m 2 / g; Silica, with a particle size ranging from 5 nm to 15 nm, is used to improve the dispersibility and pore wall stability of materials, ensuring the uniformity of bubble structure and enhancing mechanical properties. The filler is a porous carbon-based material with a specific surface area ranging from 500 m². 2 / g~1500m 2 / g is used to enhance the absorbency and sound insulation of the foam, while also providing additional structural support. By limiting the particle size and specific surface area range of these components, the foam exhibits superior sweat absorption and sound insulation properties.
[0016] Preferably, the gas inducing agent is expandable polystyrene microspheres with a particle size range of 5 μm to 10 μm, and the aluminum flame retardant powder is selected from aluminum hydroxide trihydrate or modified aluminum flame retardant powder with a particle size range of 0.5 μm to 10 μm. The gas-inducing agent, with a particle size range of 5μm to 10μm, is used to control the bubble formation process, ensuring a uniform pore distribution. Furthermore, the flame-retardant properties of the material are enhanced by selecting aluminum-based flame-retardant powders with a particle size range of 0.5μm to 10μm, while maintaining the flexibility of the foam. These limitations ensure that the material possesses both safety and processing adaptability, while simultaneously enhancing the overall stability of the pore structure.
[0017] A method for preparing breathable, sweat-absorbing, and sound-absorbing foam for car seats, according to any one of claims 1-5, is characterized by comprising the following steps: S1. Component preparation: Mix low-viscosity vinyl silicone oil, silica, aluminum flame retardant powder, and dynamic crosslinking regulator in a mixer and vacuum stir for 30-50 minutes. Then mix high-viscosity vinyl silicone oil, pore orientation agent, and filler, and degas after high-speed shear stirring for 20-40 minutes. Finally, mix gas inducer with vinyl silicone rubber and crosslinking inhibitor, pour into a mixer, and stir at a constant temperature. S2, Dynamic Crosslinking: Mix the low-viscosity vinyl silicone oil mixture in S1 with the gas inducer, then put it into a mixer and stir it evenly at 13℃~15℃. Gradually add the high-viscosity vinyl silicone oil mixture to form a dynamic crosslinking system. S3, Initial foaming: The mixture is coated onto the surface of the release film using a gradient coating device and foamed at 70℃~90℃; S4. Secondary foaming: The material is transferred to a high-temperature space and expanded foaming gas is introduced for dynamic shaping, which lasts for 2 to 4 hours; S5. Surface finishing: After peeling off the release film, the foam material is cut and finished. Step S1 involves a combination of vacuum stirring, high-speed shear stirring, and isothermal stirring to ensure uniform dispersion of low-viscosity and high-viscosity vinyl silicone oil, silica, aluminum-based flame retardant powder, and pore-oriented agent. Vacuum stirring removes air bubbles during mixing and ensures good wettability of powders such as silica. High-speed shear stirring further disperses the high-viscosity components, while isothermal stirring maintains a stable temperature in the mixture, preventing premature crosslinking reactions. Step S2, dynamic crosslinking, involves the gradual addition of the high-viscosity vinyl silicone oil mixture, combined with the action of dynamic crosslinking regulators and catalysts, to construct a crosslinked network with dynamic characteristics at 13℃–15℃. This step not only provides the chemical reaction basis for subsequent foaming but also ensures the fluidity and reaction uniformity of the system. S3, the initial foaming stage, uses a gradient coating device to control the coating thickness and foams at 70℃~90℃, initially generating a uniform pore structure. In this step, the CO2 concentration (1%~3%) regulates the bubble formation rate and size distribution, while the synergistic effect of silica and pore-orienting agents stabilizes the pore wall morphology. The pore uniformity at this stage directly affects the quality of subsequent pore expansion. S4, the secondary foaming stage, utilizes a high-temperature environment of 150℃~180℃ combined with NH3 expanding gas (concentration 0.5%~1.0%) to further expand and connect the pore structure of the initial foaming. The high-temperature conditions ensure the full progress of the dynamic cross-linking reaction, and the expanding effect of NH3 optimizes pore connectivity and size controllability. This step significantly improves the sound insulation and air permeability of the foam. The final S5 surface finishing step involves peeling off the release film and surface cutting and finishing the foam material, ensuring consistency in thickness and appearance while releasing internal residual stress, thereby improving the long-term stability of the foam. The steps work closely together, and through the synergistic effect of mixing, cross-linking, primary foaming, secondary foaming and finishing, an optimized path from components to finished product is achieved, ultimately giving the foam good structural stability and multifunctionality.
[0018] Preferably, in step S1, the mixing ratio of low-viscosity vinyl silicone oil to high-viscosity vinyl silicone oil is 2:1. During vacuum stirring, the mixer speed is 1000 rpm to 1500 rpm. During high-speed shear stirring, the mixer speed is 3000 rpm to 5000 rpm. During constant-temperature stirring, the mixer speed is 800 rpm to 1200 rpm.
[0019] The mixing ratio of low-viscosity to high-viscosity vinyl silicone oil is 2:1 to ensure that the material has both good flowability and structural support properties. Vacuum stirring at speeds ranging from 1000 rpm to 1500 rpm effectively removes air bubbles and ensures uniform dispersion of powders such as silica. High-speed shear stirring at speeds ranging from 3000 rpm to 5000 rpm disperses high-viscosity materials, while isothermal stirring at speeds ranging from 800 rpm to 1200 rpm prevents overheating and ensures uniform and stable mixing. These stirring conditions directly affect the material's performance in the subsequent foaming stage.
[0020] Preferably, in step S3, the coating thickness during gradient coating is divided into a top layer of 2mm to 3mm, a middle layer of 3mm to 5mm, and a bottom layer of 5mm to 8mm.
[0021] The gradient coating thickness range allows for multi-layered functional distribution of the foam. A thinner top layer improves breathability, a moderately thick middle layer enhances sweat absorption, while a thicker bottom layer provides sound insulation and cushioning. These limitations enable the foam to achieve optimal performance in different functional areas according to usage requirements, fully demonstrating the material's application value.
[0022] Preferably, in step S3, the foaming time is 30 min to 40 min, the foaming gas is CO2, and the concentration is 1.5% to 2.5%. The initial foaming time range of 30–40 min and the CO2 concentration range of 1.5%–2.5% are used to precisely control the bubble formation rate and size distribution. The appropriate time range ensures uniform bubble expansion and initial solidification, while the controlled CO2 concentration prevents excessive bubble formation or collapse, ensuring the basic uniformity and stability of the pore structure. These constraints provide reliable prerequisites for optimizing the secondary foaming stage.
[0023] Preferably, in step S4, the temperature range of the high-temperature space is 150℃~180℃, and the concentration of the extended foaming gas NH3 is 0.5%~1.0%; By limiting the secondary foaming temperature range to 150℃–180℃ and expanding the concentration range of the foaming gas NH3 to 0.5%–1.0%, the connectivity of the pore network and the overall structural properties of the material were optimized. High-temperature conditions allowed the dynamic cross-linking reaction to proceed fully, forming a stable network structure, while the controlled NH3 concentration further enhanced the pore expansion effect. These limitations ensured the consistency and reliability of the foam's final performance, including breathability, sweat absorption, and sound insulation.
[0024] Breathable, sweat-absorbing, and sound-absorbing foam for car seats and its preparation method. It has the following beneficial effects: 1. This invention utilizes the synergistic effect of a dynamic crosslinking regulator and a platinum catalyst to gradually construct a stable dynamic network structure during the crosslinking reaction of low-viscosity and high-viscosity vinyl silicone oils. This achieves the technical effect of simultaneously ensuring the flowability of foam processing and the stability of its pore structure. Compared to the problems of uneven crosslinking or uncontrolled reaction rates caused by single crosslinking methods in existing technologies, this invention solves the shortcomings of difficult-to-control crosslinking rate and uneven foam pores, significantly improving the mechanical properties and reliability of foam.
[0025] 2. This invention achieves optimized pore formation and distribution, and realizes a multi-layered functional gradient structure, through the design of the concentration ratio of primary foaming gas CO2 and extended foaming gas NH3, and the gradient coating thickness distribution. Compared with the problems of uneven pore distribution and single function caused by the single foaming gas or inaccurate concentration range in the prior art, this invention solves the shortcomings of uneven pore size and difficulty in controlling the structure, while ensuring the synergistic optimization of the foam's breathability, sweat absorption and sound insulation performance.
[0026] 3. This invention achieves the technical effect of improving the sweat absorption performance, sound insulation performance and structural strength of foam through the rational selection and ratio design of fumed silica and porous carbon-based materials. Compared with the existing technology, which has the problem of single function of filler and limited improvement of adsorption capacity and mechanical properties, this invention solves the shortcomings of foam in high humidity environment, such as poor adsorption capacity, insufficient sound insulation effect and insufficient pore wall strength, thereby significantly enhancing the functional stability of foam in complex use environment.
[0027] 4. By clearly defining the parameter ranges for stirring speed, foaming time and temperature, foaming gas concentration, and coating thickness, the invention achieves high uniformity in the foam preparation process, strong controllability of the reaction, and consistent final performance. Compared with the problems of large fluctuations in foam performance and poor repeatability caused by imperfect process parameters in the prior art, this invention solves the shortcomings of lack of precise parameter guidance in the preparation process and unstable performance of finished products, and significantly improves the consistency of product quality and the operability of mass production. Attached Figure Description
[0028] Figure 1This is a flowchart of the method of the present invention. Detailed Implementation
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0030] Example 1: Preparation of basic foam. Purpose: To achieve uniform pore distribution and good air permeability of foam through dynamic cross-linking control and gas regulation system.
[0031] Specific steps: S1 group allocation system: Add 50 parts of low-viscosity vinyl silicone oil (viscosity 500 mPa·s), 90 parts of silica, 140 parts of aluminum flame retardant powder (particle size 1 μm), and 2 parts of dynamic crosslinking regulator into a mixer and stir under vacuum for 30 minutes at a speed of 1200 rpm.
[0032] 30 parts of high-viscosity vinyl silicone oil (viscosity 1000 mPa·s) were mixed with 2 parts of pore-orienting agent (fluorinated block copolymer) and 15 parts of porous carbon-based filler (specific surface area 1000 m²). 2 Mix (g) and shear mix at high speed for 20 minutes at a speed of 4000 rpm.
[0033] Mix 10 parts of gas inducer (particle size 8μm) with vinyl silicone rubber and 0.5 parts of crosslinking inhibitor, and stir at a constant temperature for 40 minutes, with the temperature controlled at 15℃ and the speed at 1000rpm.
[0034] S2 dynamic crosslinking: The low-viscosity silicone oil mixture and the gas-inducing agent slurry were mixed at a ratio of 2:1 and stirred at 13°C for 25 minutes. The high-viscosity silicone oil mixture was then gradually added to form a dynamic crosslinking system.
[0035] S3 initial foaming: The mixture is coated onto the release film with a thickness of 3 mm for the top layer, 5 mm for the middle layer, and 8 mm for the bottom layer. The concentration of CO2 in the foaming gas is controlled at 2%, and the film is foamed at 80°C for 40 minutes.
[0036] S4 secondary foaming: The foaming material was placed in a high-temperature space at 170°C, and NH3 expansion gas with a concentration of 0.8% was introduced for 3 hours.
[0037] S5 Surface Finishing: After peeling off the release film, the foam is cut and trimmed to a thickness of 10mm, and left to stand for 24 hours to complete stress release.
[0038] Summarize: This embodiment ensures the uniformity of pore distribution through dynamic cross-linking control, and the gas regulation system makes the bubble structure stable and controllable, which significantly improves the air permeability of the foam. Compared with the problem of uneven bubble distribution in the prior art, it solves the shortcomings of uneven pore distribution and poor product stability.
[0039] Example 2: Preparation of sweat-absorbing foam. Purpose: To improve the sweat absorption performance and humidity regulation ability of foam by optimizing the filler and pore structure.
[0040] Specific steps: S1 group allocation system: 70 parts of low-viscosity vinyl silicone oil (viscosity 800 mPa·s) were mixed with 130 parts of silica (particle size 10 nm), 150 parts of aluminum-based flame retardant powder (modified aluminum hydroxide trihydrate) and 3 parts of dynamic crosslinking regulator, and stirred under vacuum for 40 minutes at a speed of 1500 rpm.
[0041] 50 parts of high-viscosity vinyl silicone oil (viscosity 2000 mPa·s) were mixed with 3 parts of pore-orienting agent (fluorinated block copolymer) and 30 parts of porous carbon-based material (specific surface area 1500 m²). 2 / g) High-speed shearing and stirring for 30 minutes at 4500 rpm.
[0042] Mix 15 parts of gas inducer (particle size 5 μm) with crosslinking inhibitor, stir at a constant temperature for 30 minutes, keeping the temperature at 15℃ and the speed at 1000 rpm.
[0043] S2 dynamic crosslinking: At 14°C, a low-viscosity silicone oil mixture and a high-viscosity silicone oil slurry were mixed in a 3:1 ratio and stirred for 30 minutes to form a dynamic cross-linked network.
[0044] S3 initial foaming: The mixture was coated onto the release film with a surface layer thickness of 2 mm, a middle layer thickness of 5 mm, and a bottom layer thickness of 8 mm. The concentration of CO2 in the foaming gas was 2.5%, and the mixture was foamed at 75°C for 35 minutes.
[0045] S4 secondary foaming: The expansion foaming process was completed by introducing 1% NH3 expansion gas into an environment of 160℃ for 4 hours.
[0046] S5 Surface Finishing: After peeling off the release film, the foam is cut to a thickness of 12mm and left to stand at 25℃ for 24 hours.
[0047] Summarize: This embodiment uses high specific surface area porous carbon-based materials and a reasonable gas conditioning system to enable the foam to have excellent adsorption capacity in high humidity environments, solving the problems of insufficient sweat absorption and poor humidity regulation of existing foams. At the same time, through coating thickness and multi-layer structure design, the sweat absorption performance is optimized layer by layer.
[0048] Example 3: Preparation of soundproof foam. Purpose: To achieve sound insulation performance of foam by expanding the foaming process and optimizing the filler.
[0049] Specific steps: S1 group allocation system: Mix 60 parts of low-viscosity vinyl silicone oil (viscosity 700 mPa·s) with 110 parts of silica (particle size 7 nm), 160 parts of aluminum flame retardant powder (particle size 5 μm) and 1 part of dynamic crosslinking regulator, and stir under vacuum for 50 minutes at a speed of 1300 rpm.
[0050] 40 parts of high-viscosity vinyl silicone oil (viscosity 3000 mPa·s) were mixed with 1.5 parts of pore-oriented agent and 20 parts of activated carbon filler (specific surface area 1200 m²). 2 / g) High-speed shearing and mixing for 25 minutes at 3000 rpm.
[0051] Mix 12 parts of gas inducer (particle size 6μm) with vinyl silicone rubber and stir at a constant temperature for 40 minutes, with the temperature controlled at 14℃.
[0052] S2 dynamic crosslinking: Low-viscosity silicone oil slurry and high-viscosity silicone oil slurry were mixed at a ratio of 2:1 at 13℃ and stirred for 35 minutes to form a dynamic cross-linked structure.
[0053] S3 initial foaming: The coating thickness was set to 3mm for the top layer, 4mm for the middle layer, and 7mm for the bottom layer. The CO2 concentration of the foaming gas was 1.8%, and the foaming was carried out at 80℃ for 40 minutes.
[0054] S4 secondary foaming: NH3 expansion gas with a concentration of 0.8% was introduced into a high-temperature environment of 150℃ and foaming was completed after 3 hours.
[0055] S5 Surface Finishing: After peeling off the release film, the foam is cut to a thickness of 10mm and left to stand for 24 hours to release stress.
[0056] Summarize: This embodiment combines a highly efficient extended foaming process with activated carbon filler to enhance the pore connectivity and sound wave absorption capacity of the foam, solving the problem of insufficient sound insulation performance and low-frequency noise blocking effect of existing foams, while maintaining good flexibility and stability.
[0057] Summary: Summarize The three embodiments optimized the breathability, sweat absorption and sound insulation performance respectively. They all solved the problems of uneven pore structure, single function and difficult processing control in the background technology by combining dynamic cross-linking, gas conditioning system and coating process, and significantly improved the overall performance and practicality of foam.
[0058] Comparative Example 1: Catalyst Deficiency in Dynamic Crosslinking System Corresponding Implementation Example: Example 1 Composition: Following the composition ratio of Example 1, 50 parts of low-viscosity vinyl silicone oil were mixed with 90 parts of silica, 140 parts of aluminum-based flame retardant powder, and 2 parts of dynamic crosslinking regulator, and stirred under vacuum for 30 minutes at 1200 rpm. 30 parts of high-viscosity vinyl silicone oil were mixed with 2 parts of pore-orienting agent and 15 parts of filler, and stirred under high-speed shear for 20 minutes at 4000 rpm. 10 parts of gas inducing agent and crosslinking inhibitor were mixed and stirred at a constant temperature for 40 minutes at 1000 rpm.
[0059] Dynamic crosslinking: Without adding a catalyst, the low-viscosity and high-viscosity silicone oil mixture is directly mixed in a 2:1 ratio, stirred for 30 minutes, and the crosslinking reaction is completed at 13°C.
[0060] Foaming and finishing: The initial foaming, secondary foaming and surface finishing were carried out according to the process conditions of Example 1.
[0061] Comparative Example 2: CO2 concentration of the initial foaming gas deviates from the range Corresponding Implementation Example: Example 1 Component preparation: The preparation was completed entirely according to the component ratio and process operation of Example 1.
[0062] Dynamic crosslinking: Follow the dynamic crosslinking steps in Example 1.
[0063] Initial foaming: During the initial foaming stage, the CO2 concentration was set to 5%, and the remaining conditions were kept consistent with those in Example 1.
[0064] Secondary foaming and finishing: Follow the secondary foaming and finishing steps in Example 1.
[0065] Comparative Example 3: Coating thickness designed as a single thickness Corresponding Implementation Example: Example 2 Component preparation: The preparation was completed entirely according to the component ratio and process operation of Example 2.
[0066] Dynamic crosslinking: Follow the dynamic crosslinking steps in Example 2.
[0067] Initial foaming: The coating thickness is uniformly adjusted to 5mm, and no gradient thickness is set for the surface, middle and bottom layers. All other conditions remain the same as in Example 2.
[0068] Secondary foaming and finishing: Follow the secondary foaming and finishing steps in Example 2.
[0069] Comparative Example 4: The specific surface area of the filler is relatively low. Corresponding Implementation Example: Example 2 Composition: Based on the composition ratio of Example 2, the specific surface area of the filler (porous carbon-based material) was adjusted to 300 m². 2 / g, with the remaining components and process conditions remaining consistent.
[0070] Dynamic crosslinking and foaming: Follow the steps of dynamic crosslinking, primary foaming and secondary foaming as described in Example 2.
[0071] Finishing: Follow the surface finishing steps in Example 2.
[0072] Comparative Example 5: Unmodified aluminum-based flame retardant powder Corresponding Implementation Example: Example 3 Composition: Based on the composition ratio of Example 3, the modified aluminum flame retardant powder was replaced with unmodified aluminum hydroxide trihydrate, while the remaining components and process conditions remained the same.
[0073] Dynamic crosslinking and foaming: Follow the steps of dynamic crosslinking, primary foaming and secondary foaming as described in Example 3.
[0074] Finishing: Follow the surface finishing steps in Example 3.
[0075] Comparative Example 6: The concentration of NH3 in the secondary foaming gas deviates from the range Corresponding Implementation Example: Example 3 Component preparation: The preparation was completed entirely according to the component ratio and process operation of Example 3.
[0076] Dynamic crosslinking and initial foaming: Follow the steps of dynamic crosslinking and initial foaming in Example 3.
[0077] Secondary foaming: The NH3 concentration was set to 2.0%, and the other secondary foaming conditions remained the same as in Example 3.
[0078] Finishing: Follow the surface finishing steps in Example 3.
[0079] Comparative experiment: Experiment 1: Dynamic Crosslinking Performance Test Experimental instructions The purpose of Experiment 1 was to verify the role of the catalyst in the dynamic crosslinking system, specifically comparing the differences in pore uniformity and compression recovery performance between the foam materials of Example 1 (with platinum catalyst) and Comparative Example 1 (without catalyst). The pore structure was observed using scanning electron microscopy (SEM), and the compression recovery performance of the foam was tested using a universal testing machine.
[0080] Experimental steps: Sample preparation: Prepare foam materials for Example 1 and Comparative Example 1, and cut 10cm×10cm×1cm samples to ensure that the sample sizes are consistent.
[0081] Pore structure testing: The samples were observed using a scanning electron microscope (SEM). The sample surface is treated with a metal coating to ensure electrical conductivity. Ten random regions were selected under SEM, and the pore diameter and pore wall thickness were recorded.
[0082] Compression recovery performance test: Using an electronic universal testing machine, compress the sample to 50% of its original thickness and hold for 10 minutes; After releasing the compressive force, record the thickness recovery rate (percentage of thickness recovered to the original thickness) of the sample within 30 seconds.
[0083] Experimental data The table below shows the test data for Example 1 and Comparative Example 1, including pore diameter (μm), pore wall thickness (μm), and compression recovery rate (%): sample Pore diameter (μm) Pore wall thickness (μm) Compression recovery rate (%) Example 1 55.3 2.1 95.2 Example 1 48.7 2.3 94.1 Example 1 52.9 2.2 96.3 Example 1 50.2 2.0 93.8 Example 1 49.8 2.4 95.7 Comparative Example 1 80.5 1.4 65.3 Comparative Example 1 75.8 1.6 63.9 Comparative Example 1 78.3 1.5 66.8 Comparative Example 1 76.1 1.8 64.2 Comparative Example 1 82.0 1.3 62.5 Table Title: Dynamic Crosslinking Performance Test Data of Example 1 and Comparative Example 1 Experimental Summary and Mechanism Analysis Experiments show that the foam material in Example 1 has a more uniform pore distribution (average pore diameter between 48.7 μm and 55.3 μm) and thicker pore walls (2.0 μm to 2.4 μm), while the pore diameter in Comparative Example 1 is larger (75.8 μm to 82.0 μm), the pore walls are thinner (1.3 μm to 1.8 μm), and the structure is non-uniform. This difference is closely related to the addition of a catalyst. The platinum catalyst used in this invention can accelerate the crosslinking reaction of vinyl silicone oil, rapidly forming a stable crosslinking network during the dynamic crosslinking process, thereby preventing the pores from over-growing or collapsing due to insufficient support during the expansion stage. In Comparative Example 1, due to the absence of a catalyst, the crosslinking reaction rate is slower, resulting in a non-uniform pore structure inside the material.
[0084] In the compression recovery performance test, the compression recovery rate of Example 1 was significantly higher than that of Comparative Example 1 (93.8%–96.3% vs. 62.5%–66.8%). This difference mainly stems from the stability of the cross-linked network. The dynamic cross-linked network of Example 1 was able to rapidly recover its original shape under high stress, while the network of Comparative Example 1, due to insufficient cross-linking, was difficult to recover after damage. This further illustrates the important role of platinum catalysts in improving the mechanical properties of foam.
[0085] The technical solution of this invention improves the uniformity of pores and mechanical properties through dynamic cross-linking control, solving the problems of uneven pores and poor compression recovery in the prior art. Mechanistically, the highly efficient catalytic effect of the platinum catalyst ensures the reaction rate and uniformity, allowing the cross-linked network to gradually form under dynamic control, providing support for the stability of the pore structure, and reducing local defects during the foaming process.
[0086] Experiment 2: Test on the relationship between pore structure and foaming gas concentration Experimental instructions The purpose of Experiment 2 is to verify the effect of the initial foaming gas CO2 concentration on the uniformity of pore structure and mechanical properties of materials. By comparing the samples of Example 1 (CO2 concentration of 2%) and Comparative Example 2 (CO2 concentration of 5%), the influence of bubble expansion behavior on pore size distribution and mechanical properties is evaluated.
[0087] Experimental steps: Sample preparation: Prepare foam materials for Example 1 and Comparative Example 2, and cut test samples of 10cm×10cm×1cm respectively to ensure that the sample sizes are consistent.
[0088] Pore structure testing: The pore structure of the sample was observed using a scanning electron microscope (SEM): Sample surface treatment: Apply a metal coating to ensure its conductivity; Ten regions were randomly selected under SEM, and the pore diameter and its distribution range of each region were recorded.
[0089] Mechanical property testing: The tensile strength of the sample was tested using an electronic universal testing machine. The sample was fixed in the fixture and stretched at a tensile speed of 10 mm / min until it broke. Record the maximum tensile strength of the sample (unit: MPa).
[0090] Experimental data The following are the test data for Example 1 and Comparative Example 2, including pore diameter range (μm), pore uniformity coefficient (ratio of maximum diameter to minimum diameter), and tensile strength (MPa): Table Title: Test Data on Pore Structure and Mechanical Properties of Example 1 and Comparative Example 2 Experimental Summary and Mechanism Analysis Experimental results show that the foam in Example 1 has a smaller and more uniform pore diameter (pore diameter range of 48.6–55.8 μm, uniformity coefficient of 1.07–1.11), while the foam in Comparative Example 2 has a larger and less uniform pore diameter (pore diameter range of 71.9–90.7 μm, uniformity coefficient of 1.15–1.24). This difference indicates that the present invention achieves uniform bubble expansion during the foaming process by controlling the CO2 concentration, solving the problem of structural instability caused by excessively rapid bubble expansion in the prior art.
[0091] Tensile strength tests showed that the tensile strength of the sample in Example 1 was significantly higher than that in Comparative Example 2 (1.66–1.71 MPa vs. 0.94–0.98 MPa). This is because in Example 1, the moderate CO2 concentration (2%) enabled the formation of a stable pore structure with uniform pore wall thickness during foaming, thereby enhancing the mechanical properties of the material. In contrast, in Comparative Example 2, the higher CO2 concentration (5%) caused the bubbles to expand too quickly, resulting in the rupture or excessive enlargement of some pores and the formation of an irregular pore distribution, which significantly reduced the mechanical properties of the material.
[0092] The mechanism of this invention lies in the precise control of CO2 concentration, ensuring that the bubble expansion rate is consistent with the formation rate of the cross-linked network, thereby preventing the bubbles from rupturing or becoming unstable due to insufficient support during expansion. By supporting bubble expansion through the stability of the dynamic cross-linked network, this invention achieves uniformity of the pore structure and optimization of the overall material performance. Experimental results fully demonstrate the significant advantages of this invention in solving the problems of uneven pore distribution and poor mechanical properties in existing technologies.
[0093] Experiment 3: Test on the effect of gradient coating on multifunctional performance Experimental instructions Experiment 3 aimed to verify the impact of gradient coating thickness design on the breathability, sweat absorption, and sound insulation performance of foam. By comparing foam samples from Example 2 (with gradient coating thickness) and Comparative Example 3 (with a single coating thickness of 5 mm), the effect of gradient coating structure on improving the multifunctional performance of foam was evaluated.
[0094] Experimental steps: Sample preparation: The foam materials of Example 2 and Comparative Example 3 were prepared, and samples of 10cm×10cm×2cm were cut for testing their breathability, sweat absorption and sound insulation performance.
[0095] Breathability test: The airflow resistance of the sample was tested using an airflow permeameter. Fix the sample onto the testing device; The air permeability of the sample was measured under a constant airflow of 5 L / min (unit: m³). 3 / s).
[0096] Sweat absorption test: The sample was immersed in simulated sweat (37°C, 0.9% NaCl solution) for 30 minutes: Dry the sample to constant weight before testing; After soaking, remove the product and use filter paper to absorb the surface moisture. Measure the water absorption rate (the ratio of the mass after water absorption to the dry mass, in %).
[0097] Sound insulation performance test: The noise attenuation coefficient of the sample was measured using an acoustic testing instrument. Place the sample in the testing device; Sound waves were gradually applied in the range of 100Hz to 1000Hz, and the noise attenuation coefficients at different frequencies were recorded.
[0098] Experimental data The following are the test data for Example 2 and Comparative Example 3, including air permeability (m³). 3 / s), water absorption rate (%) and noise attenuation factor (dB): Table Title: Multifunctional Performance Test Data of Example 2 and Comparative Example 3 Experimental Summary and Mechanism Analysis Experimental data show that the air permeability of the sample in Example 2 is (0.048–0.053 m³ / s). 3 The air permeability (ρ / s), water absorption rate (312.6–320.1%), and noise reduction coefficient (27.8–29.2 dB) of Comparative Example 3 were all significantly higher than those of Comparative Example 3 (0.031–0.035 m³ / s). 3 The differences in absorbency (275.9–283.4%) and noise reduction factor (20.8–22.1 dB) are primarily due to the optimization of the multifunctional performance of the foam by the gradient coating thickness design in this invention. In Example 2, the thinner top coating (2 mm) improves breathability, the moderate coating thickness in the middle layer (5 mm) enhances sweat absorption, and the thicker bottom coating (8 mm) provides better sound insulation. This layered design allows for gradient optimization of the foam's performance to meet different functional requirements.
[0099] In the breathability test, the high breathability of the sample in Example 2 was directly related to the thin design of the gradient coating surface layer. The thinner surface layer structure reduced the resistance to gas passage, while the uniform thickness (5 mm) design in Comparative Example 3 restricted airflow, resulting in poor breathability. The sweat absorption test showed that the moderate thickness design of the middle layer in Example 2 created a large adsorption capacity, while the uniformity of the pore structure ensured rapid water transfer; whereas the uniform thickness design in Comparative Example 3 weakened the adsorption capacity, leading to decreased sweat absorption. In the sound insulation test, the thick bottom coating of Example 2 significantly enhanced sound wave absorption, especially the attenuation of low-frequency noise, while Comparative Example 3, lacking a layered design, had limited sound insulation performance.
[0100] The mechanism of this invention lies in using a gradient coating thickness design to allow different layers of the foam to fulfill specific functional requirements. A thin surface coating reduces airflow resistance, a moderately thick middle layer enhances water absorption, and a thick bottom coating provides superior sound absorption. This design not only achieves multi-functional synergistic optimization of the foam but also solves the problem of single-function foaming and difficulty in simultaneously achieving multiple performance characteristics in existing technologies. Experimental results further verify the significant advantages of this invention's technical solution in terms of breathability, sweat absorption, and sound insulation.
[0101] Experiment 4: Sweat Absorption Performance Test Experimental instructions Experiment 4 aimed to verify the effect of the specific surface area of the filler on the sweat absorption performance of the foam, by comparing it with Example 2 (filler specific surface area of 1000m²). 2 / g) and Comparative Example 4 (filler specific surface area is 300m²) 2 We evaluated the role of porous fillers in sweat absorption and moisture conduction properties using samples of / g).
[0102] Experimental steps: Sample preparation: The foam materials of Example 2 and Comparative Example 4 were prepared, and samples of 10cm×10cm×1cm were cut for sweat absorption performance testing.
[0103] Sweat-wicking performance test: Prepare a simulated sweat solution (37°C, 0.9% NaCl solution by mass), ensuring the liquid temperature remains constant; After drying the sample to constant weight, record the drying mass. After immersing the sample in simulated sweat for 30 minutes, remove it and quickly absorb the surface moisture with filter paper. Measure the wet weight of the sample Calculate the water absorption rate; Data duplication: Each sample was tested three times, and the average value was taken. The water absorption rate was recorded for each test.
[0104] Experimental data The following are the test data for Example 2 and Comparative Example 4, including the water absorption rate (%) for each test: sample Test 1: Water absorption rate (%) Test 2: Water absorption rate (%) Test 3: Water absorption rate (%) Example 2 325.3 318.9 322.7 Example 2 319.5 320.4 324.1 Example 2 323.0 317.6 326.5 Comparative Example 4 278.4 273.1 280.6 Comparative Example 4 275.3 279.2 277.5 Comparative Example 4 272.7 276.9 278.3 Table Title: Sweat Absorption Performance Test Data of Example 2 and Comparative Example 4 Experimental Summary and Mechanism Analysis Experimental data show that the water absorption rate of the sample in Example 2 was significantly higher than that of Comparative Example 4, with average water absorption rates of 322.3% and 277.4%, respectively. This difference is mainly due to the direct influence of the different specific surface area of the filler on the sweat absorption performance of the foam. In Example 2, the specific surface area of the porous carbon-based filler was 1000 m². 2 / g, which provides larger internal pores and more adsorption sites, effectively adsorbing and storing moisture; while the filler in Comparative Example 4 has a specific surface area of only 300m². 2 / g, with limited pore capacity and adsorption capacity, resulting in poor sweat absorption performance.
[0105] In this experiment, the sweat-absorbing performance advantage of Example 2 is not only reflected in its higher water absorption capacity, but also in the uniformity and speed of water absorption. The filler with a higher specific surface area enhances the adsorption capacity of the interconnected pores within the foam, while effectively transferring moisture and avoiding localized oversaturation of the pores. In contrast, in Comparative Example 4, the pore distribution is smaller and less interconnected, resulting in lower water absorption efficiency and greater fluctuations in the water absorption rate during the experiment.
[0106] The mechanism of this invention lies in the synergistic effect of a high specific surface area filler and a porous structure. In Example 2, the filler combines with the dynamic cross-linked network of the foam through its microporous surface, forming a multi-layered adsorption system. This system, on the one hand, expands the foam's ability to capture water molecules, and on the other hand, improves moisture conduction efficiency and storage capacity by optimizing pore distribution and network connectivity. This invention solves the problem of low sweat absorption capacity caused by insufficient filler performance in the prior art, providing technical support for the widespread application of foam in high humidity environments. Experimental results fully verify the sweat absorption performance advantages of this invention.
[0107] Experiment 5: Flame Retardant Performance Test Experimental instructions Experiment 5 aims to verify the effect of aluminum-based flame retardant powder modification on the flame retardant properties of foam. By comparing the samples of Example 3 (modified aluminum-based flame retardant powder) and Comparative Example 5 (unmodified aluminum-based flame retardant powder), the effect of flame retardant material modification on inhibiting combustion and enhancing material safety is evaluated.
[0108] Experimental steps: Sample preparation: The foam materials of Example 3 and Comparative Example 5 were prepared, and samples of 10cm×10cm×2cm were cut for combustion performance testing.
[0109] Combustion test: The flame retardant properties of the foam were tested using a UL-94 horizontal flammability tester. Fix the sample on the combustion fixture, 10mm away from the flame; Ignite the sample and apply the flame for 10 seconds, then remove it and record the burning time. Measure the char length (cm) of the sample and observe whether the combustion is self-extinguishing.
[0110] Test settings: The flame height is set to 20mm, and the burning time is 10 seconds. Each sample group was tested three times, and the combustion time and char length were recorded.
[0111] Experimental data The following are the combustion time and char length data (unit: seconds / cm) for Example 3 and Comparative Example 5: Table Title: Flame Retardant Performance Test Data of Example 3 and Comparative Example 5 Experimental Summary and Mechanism Analysis Experimental results show that the average burning time of Example 3 was 3.2 seconds, and the char length was 1.7–1.9 cm, significantly better than the average burning time (8.4–8.6 seconds) and char length (4.1–4.3 cm) of Comparative Example 5. The advantages of the modified aluminum-based flame retardant powder are reflected in the significant improvement in combustion inhibition efficiency and the significant reduction in the char area, proving its enhancing effect on the flame retardant performance of foam. In Example 3, the modified aluminum-based flame retardant powder improved its dispersibility and interfacial compatibility with the silicone oil matrix through surface treatment, allowing it to be more evenly distributed inside the foam, thereby forming a uniform flame retardant barrier during combustion. In contrast, in Comparative Example 5, the unmodified flame retardant powder had poor dispersibility and insufficient local flame retardant effect, resulting in a longer burning time and a larger char area.
[0112] During combustion, the flame-retardant mechanism of modified aluminum-based flame-retardant powder mainly includes heat absorption and cooling, as well as carbonization protection. In the experiment, the foam sample of Example 3 released water of crystallization when heated, absorbing a large amount of heat, significantly reducing the temperature rise of the material surface and inhibiting the continued spread of combustion. At the same time, the modified flame-retardant powder promoted the formation of a dense carbonized layer on the material surface, which further isolated the oxygen supply and prevented the spread of flame. In contrast, the unmodified flame-retardant powder in Comparative Example 5 had weaker heat absorption and cooling capacity and carbonized layer formation effect, resulting in a longer combustion time, a loose carbonized layer, and uneven coverage.
[0113] The technical solution of this invention solves the problems of poor dispersibility and weak interfacial bonding of flame retardant powders in existing technologies by utilizing the highly efficient flame retardant mechanism of modified aluminum-based flame retardant powders, thus achieving excellent flame retardant performance in foam materials. Simultaneously, the improved dispersion uniformity and heat absorption efficiency of the modified flame retardant powder enhance the safety of the foam in practical applications. Experimental results fully verify the significant advantages of this invention in optimizing flame retardant performance.
[0114] Experiment 6: Sound Insulation Performance Test Experimental instructions The purpose of Experiment 6 was to verify the effect of the concentration of foaming gas NH3 on the sound insulation performance of foam. By comparing the samples of Example 3 (NH3 concentration of 0.8%) and Comparative Example 6 (NH3 concentration of 2.0%), the role of expanded foaming gas in the formation of foam pore network and sound wave attenuation was evaluated.
[0115] Experimental steps: Sample preparation: The foam materials of Example 3 and Comparative Example 6 were prepared, and samples of 10cm×10cm×2cm were cut for sound insulation performance testing.
[0116] Sound insulation performance test: The noise attenuation capability of the sample was tested using an acoustic testing instrument. The sample is placed in the acoustic wave transmission channel with an incident angle of 90°. Different frequencies of sound waves (100Hz, 500Hz, 1000Hz, 1500Hz, 2000Hz) are applied sequentially. Record the difference in sound pressure level before and after the sample, and calculate the noise attenuation coefficient (unit: dB).
[0117] Test settings: The test sound pressure level was set to 90dB; Each group of samples was tested three times, and the average value was taken.
[0118] Experimental data The following are the noise attenuation coefficient (unit: dB) test data for Example 3 and Comparative Example 6: sample 100Hz 500Hz 1000Hz Example 3 12.8 18.6 25.2 Example 3 13.1 17.9 24.8 Example 3 12.9 18.3 25.0 Comparative Example 6 8.3 12.4 17.6 Comparative Example 6 8.6 13.1 18.2 Comparative Example 6 8.5 12.8 18.0 Table Title: Sound Insulation Performance Test Data of Example 3 and Comparative Example 6 Experimental Summary and Mechanism Analysis Experimental results show that the noise attenuation coefficient of the sample in Example 3 is significantly higher than that of Comparative Example 6 at all frequencies. Especially in the mid-to-high frequency range (1000Hz–2000Hz), the attenuation coefficient of Example 3 reaches 25.0–33.4dB, while that of Comparative Example 6 is only 17.6–25.1dB. This significant difference is mainly due to the influence of the different concentrations of the expanding foaming gas NH3 on the connectivity and structural uniformity of the foam pore network. In Example 3, the NH3 concentration is 0.8%, which is a relatively moderate gas concentration that can promote the uniform expansion of pores during the foaming process, forming a stable porous network structure, thereby effectively absorbing and attenuating sound wave energy. In contrast, the NH3 concentration in Comparative Example 6 is as high as 2.0%, resulting in an excessively fast foaming rate, uneven pore size distribution, and poor pore connectivity in some areas, thus weakening the foam's ability to absorb sound waves.
[0119] In the low-frequency range (100Hz–500Hz), Example 3 exhibited a higher noise attenuation coefficient, ranging from 12.8 to 18.6 dB. This was mainly due to the optimized pore structure's reflection and multiple scattering of low-frequency sound waves. In contrast, the non-uniform distribution of the pore structure in Comparative Example 6 resulted in enhanced penetration of some sound waves, leading to an attenuation coefficient of only 8.3–13.1 dB. In the high-frequency range (1500Hz–2000Hz), the sample from Example 3 demonstrated superior sound absorption capabilities, with an attenuation coefficient reaching 30.5–33.4 dB. This is closely related to the absorption and conversion capabilities of the highly interconnected pore network for sound energy.
[0120] The mechanism of this invention lies in achieving simultaneous optimization of pore expansion and cross-linked network construction through precise control of the concentration of the expanding foaming gas NH3. In Example 3, a moderate NH3 concentration not only promoted uniform pore expansion but also ensured the connectivity of the pore network, enhancing the scattering and absorption of sound waves. In contrast, the excessively high NH3 concentration in Comparative Example 6 led to uncontrolled foaming, uneven pore structure, and the formation of excessively large or closed pores in some areas, weakening the absorption capacity of sound waves. These experimental results fully verify the significant advantages of the technical solution of this invention in optimizing sound insulation performance, especially its application potential in multi-band noise attenuation.
[0121] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A breathable, sweat-absorbing, and sound-absorbing foam for car seats, characterized in that, Includes the following components: 50-70 parts of low-viscosity vinyl silicone oil; 30 to 50 parts of high-viscosity vinyl silicone oil; 90 to 130 parts of silica; 140-160 parts of aluminum-based flame retardant powder; 1 to 3 parts of dynamic crosslinking regulator; Catalyst: 0.3 to 0.5 parts; Pore orienting agent: 1.5 to 3 parts; 10 to 30 parts of filler; 5 to 15 parts of gas inducer.
2. The breathable, sweat-absorbing, and sound-absorbing foam for car seats according to claim 1, characterized in that, The gas conditioning system used for the component materials includes: The primary foaming gas is CO2, with a concentration of 1% to 3%. The foaming gas NH3 has a concentration of 0.5% to 1.5%. The gas inducer is expandable polystyrene microspheres with a particle size range of 5µm to 10µm; The catalyst used is a platinum catalyst.
3. The breathable, sweat-absorbing, and sound-absorbing foam for car seats according to claim 1, characterized in that, The low-viscosity vinyl silicone oil has a viscosity of 500 mPa·s-800 mPa·s, and the high-viscosity vinyl silicone oil has a viscosity of 1000 mPa·s-3000 mPa·s. The pore orientation agent is a fluorinated block copolymer, and the dynamic crosslinking regulator is a mercapto compound.
4. The breathable, sweat-absorbing, and sound-absorbing foam for car seats according to claim 1, characterized in that, The silica is fumed silica with a particle size range of 5 nm to 15 nm, and the filler is a porous carbon-based material with a specific surface area of 500 m² / g to 1500 m² / g.
5. The breathable, sweat-absorbing, and sound-absorbing foam for car seats according to claim 1, characterized in that, The gas inducer is expandable polystyrene microspheres with a particle size range of 5µm to 10µm, and the aluminum-based flame retardant powder is selected from aluminum hydroxide trihydrate or modified aluminum-based flame retardant powder with a particle size range of 0.5µm to 10µm.
6. A method for preparing a breathable, sweat-absorbing, and sound-absorbing foam for car seats, according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Component preparation: Mix low-viscosity vinyl silicone oil, silica, aluminum flame retardant powder, and dynamic crosslinking regulator in a mixer and vacuum stir for 30-50 minutes. Then mix high-viscosity vinyl silicone oil, pore orientation agent, and filler, and degas after high-speed shear stirring for 20-40 minutes. Finally, mix gas inducer with vinyl silicone rubber and crosslinking inhibitor, pour into a mixer, and stir at a constant temperature. S2, Dynamic Crosslinking: Mix the low-viscosity vinyl silicone oil mixture in S1 with the gas inducer, then put it into a mixer and stir it evenly at 13℃~15℃. Gradually add the high-viscosity vinyl silicone oil mixture to form a dynamic crosslinking system. S3, Initial foaming: The mixture is coated onto the surface of the release film using a gradient coating device and foamed at 70℃~90℃; S4. Secondary foaming: The material is transferred to a high-temperature space and expanded foaming gas is introduced for dynamic shaping, which lasts for 2 to 4 hours. S5. Surface finishing: After peeling off the release film, the foam material is cut and finished.
7. The method for preparing breathable, sweat-absorbing, and sound-absorbing foam for automobile seats according to claim 6, characterized in that, In step S1, the mixing ratio of low-viscosity vinyl silicone oil to high-viscosity vinyl silicone oil is 2:
1. During vacuum stirring, the mixer speed is 1000 rpm to 1500 rpm. During high-speed shear stirring, the mixer speed is 3000 rpm to 5000 rpm. During constant-temperature stirring, the mixer speed is 800 rpm to 1200 rpm.
8. The method for preparing breathable, sweat-absorbing, and sound-absorbing foam for automobile seats according to claim 6, characterized in that, In step S3, the coating thickness during gradient coating is divided into surface layer 2mm-3mm, middle layer 3mm-5mm, and bottom layer 5mm-8mm.
9. The method for preparing a breathable, sweat-absorbing, and sound-absorbing foam for automotive seats according to claim 6, characterized in that, In step S3, the foaming time is 30 min to 40 min, the foaming gas is CO2, and the concentration is 1.5% to 2.5%.
10. The method for preparing a breathable, sweat-absorbing, and sound-absorbing foam for automotive seats according to claim 6, characterized in that, In step S4, the temperature range of the high-temperature space is 150℃~180℃, and the concentration of the extended foaming gas NH3 is 0.5%~1.0%.